Applied Data Science for Testing the Impact of Intangible Resources on Business Performance of SMEs - Le Dinh Hac; Phan Thanh Tam (Bright Publisher, 2026)
This study investigates how intangible resources influence business performance in small and medium-sized enterprises in Vietnam by applying structural equation modeling within an applied data science framework. The research aims to clarify the direct and indirect mechanisms through which key intangible components, such as human capital, structural capital, relationship capital, organizational culture, and brand image, shape enterprise outcomes. It also examines the mediating role of creative innovation and the moderating influence of operating time. The study employs a mixed-method design, beginning with qualitative interviews with enterprise managers to validate and refine measurement constructs, followed by a quantitative survey of managers in two major economic regions in Vietnam. Data were analyzed using an advanced structural modeling approach to assess reliability, validity, and the strength of causal relationships. The findings demonstrate that intangible resources act as a robust foundation for firm success, exerting strong positive effects on both creative innovation and overall business performance. All five resource dimensions significantly contribute to the higher-order construct, with relationship capital and organizational culture emerging as the most influential drivers. Creative innovation partially mediates the relationship between intangible resources and business performance, illustrating how firms convert knowledge-based assets into tangible outcomes through idea generation and implementation. Further, operating time strengthens this relationship, indicating that more established firms leverage their intangible foundations more effectively. The study contributes to ongoing discussions on resource-based competitiveness by extending theoretical perspectives to an emerging market context. It highlights the strategic importance of cultivating intangible resources to foster innovation capability and sustain long-term performance. The results offer practical implications for managers and policymakers seeking to develop knowledge-driven and innovation-oriented enterprises in dynamic economic environments.